2022
DOI: 10.1177/09636897221081487
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Efficacy Study of Multiple Allogeneic Canine Adipose Tissue-Derived Mesenchymal Stem Cells Transplantations Combined With Surgery in Four Dogs With Lumbosacral Spinal Cord Injury

Abstract: Severe lumbosacral pain, paraparesis or paraplegia, and urinary incontinence are common but frustrating problems in dogs with lumbosacral spinal cord injury (SCI). The surgical interventions including stabilization and decompression may not restore satisfying neurological functions in severe SCI. Adipose tissue-derived mesenchymal stem cells (Ad-MSCs) show benefits in immunomodulation, anti-inflammation, and promotion of axonal growth and remyelination, and also display efficacy in several diseases in veterina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…The usual treatment in companion animals involves surgical stabilization or decompression, which includes the removal of diseased intervertebral disc material. However, recovery rates are variable and often unsatisfactory, failing to successfully restore neurological functions in the most severe cases [41]. Therefore, new therapeutic alternatives are required to reduce inflammation and promote tissue regeneration.…”
Section: Neuromuscular Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The usual treatment in companion animals involves surgical stabilization or decompression, which includes the removal of diseased intervertebral disc material. However, recovery rates are variable and often unsatisfactory, failing to successfully restore neurological functions in the most severe cases [41]. Therefore, new therapeutic alternatives are required to reduce inflammation and promote tissue regeneration.…”
Section: Neuromuscular Diseasesmentioning
confidence: 99%
“…The characteristic anti-inflammatory and trophic activities of MSCs, along with their ability to stimulate axonal growth, remyelination, and cell proliferation, could be a stimulus for the regeneration process in damaged tissues [41,42]. However, to date, the results obtained in different studies display considerable variability due to several reasons.…”
Section: Neuromuscular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…One key area needing investigation is the development of methods for enhancing the intrinsic regenerative capacity of injured axons [76]. Indeed, the transplantation of AT-MSCs in various SCI animal models has shown beneficial effects on immunomodulation, inflammation, and the promotion of re-myelination and axonal growth [77][78][79][80].…”
Section: Neurologic Diseasesmentioning
confidence: 99%
“…Stem cell transplantation is a promising approach to promote recovery of injuries or degenerative changes after SCI. Over the past two decades, several clinical and preclinical studies have reported that adipose-derived mesenchymal stem cells (ADSCs) have tremendous neuroprotective and regenerative potentials after SCI when delivered directly to the lesioned cavity that forms after injury [ 7 , 8 ]. Presently, ADSC injection and ADSC seeding in scaffold materials are the two most commonly used methods with the drawbacks of transplanted cell loss and death, and inflammatory reactions of the scaffolds, which limit their application in SCI repair [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%